Forging artistic value (Lebenswelt. Aesthetics and philosophy of experience., 2025)
The prevailing attitude towards forgeries is that they have a basic aesthetic value derived from sensory reward and a power to please but no value as art. This essay is a reply to this standard view. It defends the distinction between aesthetic and artistic value and argues that, as well as having equal aesthetic value to original artworks, forgeries can also have artistic value. They can become valuable as an artwork in some of the same ways that originals do, but they can also accrue artistic value as a forgery for the accuracy of their representation of a referent.